Pengaplikasian Sistem Rekrutmen dan Seleksi Untuk Meningkatkan Komitmen Kerja Karyawan - Julia Tiana; Julia Salsabila; Sri Wahyuni; Shanty Komalasari (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
One of the ways companies get prospective workers who have high work results is by manifesting the recruitment and selection process. An agency needs to recruit prospective workers who match the criteria needed with the aim of being able to carry out the job desks that have been determined in certain positions. Finding prospective workers who have competencies and criteria that are in accordance with the needs of an agency is quite complicated so it requires a special scheme during the recruitment and selection process. This research discusses whether the recruitment and selection system has an influence on employee work commitment, this research uses a literature study method that examines several sources that examine the application of the recruitment and selection system to increase employee work commitment.